ILRI's partnership strategy and management system - International Livestock Research Institute (International Livestock Research Institute, 2008)
In 2003, ILRI published the new centre strategy for its research and development activities. This strategy moved away from the conventional view of research, as a rather linear and often isolated process, to the pursuit of impact as a driving force for research with the perspective of innovation systems as a framework. The strategy recognizes the complexity of innovation as a socio-technical process where both knowledge networks and networks of infl uence are central to success in a continuous transformation process. A new way of doing science is the consequence of this commitment to impact-driven engagement in research for development. Partnerships among multiple actors are at the centre of such an approach to science and ILRI';s strategy highlights working through partnerships. The goal of ILRI';s strategy emphasizes the integration of science, capacity building and partnerships as a vehicle for impact. After three years of implementation of the new strategy, ILRI Management recognized the need for an in-depth analysis of the state of its partnerships and initiated a Centre Commissioned External Review. An initial short study revealed that, whilst considerable progress had been made, the management of partnerships needed to move from a rather ad hoc approach to one that was more proactive and systematic. The Management decided to pursue the development of a more coherent partnership strategy and management system which aims at institutionalization and operationalization of effective partnership management in the organizational structures, systems and processes. ILRI anticipated that by the end of this development and institutionalization process, ILRI would have a much clearer understanding of its partnerships and would be in a position to improve their quality in partnership management at all levels, thereby increasing its effi ciency and effectiveness. The approach chosen to develop the partnership strategy focused on the commitment and ownership of ILRI staff. An internal task force was formed, guided by an external process consultant. The process included the analysis and conceptualization of experiences and perspectives of stakeholders (a survey was carried out), lesson learning from successful and failed examples and exploring approaches practised elsewhere. Institutionally, the administrative systems were analysed in regard to their role in supporting partnership management and where necessary the systems were adapted. The product coming out of this analytical process by the task force is this guide to ILRI';s partnerships: a dynamic working document which will be regularly revisited and complemented as ILRI further professionalizes its partnership management with new instruments and mechanisms in a learning mode.